(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The dynamics of different treatment methods with different treatment methods was assessed in 120 patients with pollen sensitization. The indicators of the quality of life of patients improved with the use of both specific and non-specific methods of treatment (p <0.05). The best results were obtained with the use of allergen-specific immunotherapy, autoserotherapy (p <0.001).